German Economy Autumn 2018 - Germany's boom is maturing - Martin Ademmer; Jens Boysen-Hogrefe; Salomon Fiedler; Dominik Groll; Nils Jannsen; Stefan Kooths; Galina Potjagailo (Kiel Institute for the World Economy (IfW), 2018)
The economic upswing in Germany continues, although the expansion loses some steam. Compared to our summer forecast, we reduced our expectations for GDP growth by 0.1 and 0.3 percentage points in the current and next year, respectively, to 1.9 percent (2018) and 2.0 percent (2019). So for now, the boom in Germany persists. However, due to the already very high capacity utilization in many sectors, companies face increasing difficulties in continuing to expand their production at a brisk pace. This is especially palpable in the construction sector where in the face of very favorable circumstances production increases were quite restrained but prices rose markedly. The labor market also exhibits increasing shortages. Not least due to this, increases in employment should reduce over time. Next year, the expansionary fiscal policy will support the boom. The extensive tax reductions and spending increases will raise disposable incomes considerably, such that private consumption expenditures should grow by 2.2 percent -the fastest in 20 years. Because of the robust world economy after the phase of weakness at the beginning of the year, exports should also accelerate again. The additional temporary revenue of public authorities due to the current business cycle position is spent hand over fist on expenditures that are intended to persist in the long-run. The currently still sizeable structural budget surplus will therefore be eradicated by the year 2020. – – Der Aufschwung in Deutschland setzt sich fort, allerdings lassen die Expansionskräfte etwas nach. Gegenüber dem Konjunkturausblick im Sommer haben wir unsere Prognose für die Zuwachsrate des Bruttoinlandsprodukts im laufenden Jahr um 0,1 Prozentpunkte und im kommenden Jahr um 0,3 Prozentpunkte heruntergenommen auf nun 1,9 Prozent (2018) bzw. 2,0 Prozent (2019). Damit hält die Hochkonjunktur in Deutschland zwar vorerst an. Angesichts der in vielen Wirtschaftsbereichen bereits hohen Kapazitätsauslastung fällt es den Unternehmen aber offenbar zusehends schwerer, ihre Produktion weiter in hohem Tempo auszuweiten. Besonders augenfällig ist dies bereits im Baugewerbe, in dem die Produktion angesichts der sehr günstigen Rahmenbedingungen nur verhalten expandiert und die Preise kräftig steigen. Auch am Arbeitsmarkt machen sich zunehmend Knappheiten bemerkbar. Nicht zuletzt deshalb dürfte sich der Beschäftigungsaufbau im Prognosezeitraum allmählich verringern. Im kommenden Jahr wird die expansive Finanzpolitik die Hochkonjunktur stützen. Die umfangreichen Abgabensenkungen und Leistungsausweitungen werden die verfügbaren Einkommen spürbar erhöhen, so dass die privaten Konsumausgaben mit 2,2 Prozent so stark zunehmen wie seit 20 Jahren nicht mehr. Auch die Exporte dürften sich aufgrund der robusten Weltkonjunktur nach der Schwächephase zu Jahresbeginn wieder beschleunigen. Die öffentlichen Haushalte geben die konjunkturell bedingt - und damit nur vorübergehend - höheren Einnahmen mit vollen Händen für dauerhaft angelegte zusätzliche Ausgaben aus. Aus diesem Grund wird sich der derzeit noch deutlich positive strukturelle Budgetsaldo unserer Einschätzung zufolge im Jahr 2020 bereits wieder in eine rote Null verwandeln.
Keywords: 330; business cycle forecast; stabilization policy; leading indicators; outlook; forecast evaluation; investment income